Spatio-temporal variation in snow cover area and its fragmentation in Northeast China - Gu, Jiakai; Ma, Yanmin; Zhang, Lijuan; Huang, Yutao; Zhang, Wenshuai; Zhang, Fan; Liu, Jie; Li, Chunyang (Frontiers in Earth Science, 2024)
Under the backdrop of climate warming and changes in snow cover area, the spatial fragmentation characteristics of snow cover need to be studied in depth. In this study, we analyzed the spatial and temporal change patterns of the snow cover area and explored the changing characteristics of its spatial fragmentation in Northeast China from 1980 to 2019 using the “China AVHRR Daily Cloudless 5 km Snow Area Product Dataset.” The findings indicate that the mean stable snow cover area in Northeast China from 1980 to 2019 was 79.41 × 104 km2 (±14.47 × 104 km2), with no significant changes observed since the 1980s. However, compared to the 1980s, mountainous areas such as the Changbai Mountain and Lesser Khingan Mountain regions were identified as the main areas of snow cover recession. The mean patch size (MPS), largest pach index (LPI) and patch size coefficient of variation (PSCV) for spatial fragmentation from 1980 to 2019 showed the following rates of change of −1.06 × 104 km2/10 a (p < 0.05), −1.04%/10 a (p > 0.05), and 71.6%/10 a (p < 0.05), respectively. The spatial continuity of snow fragmentation in Northeast China has significantly increased, with fragmentation showing significant growth. From 2010 to 2019, the spatial fragmentation of snow cover in Northeast China increased by 50% compared to the 1980–1989 period. This paper suggests that the increase in temperature is the major factor leading to the fragmentation of snow cover. The main contribution of this paper is the analysis of the change characteristics of the spatial fragmentation in regional snow cover.